Implementation of DSP-based fuzzy neural network-PI controller for PMSM - Gencer, Cetin (Sila Science, 2012)
An improved Fuzzy Neural Network Proportional Integral (FNN-PI) controller based on Sugeno fuzzy model is proposed in this paper for Permanent Magnet Synchronous Motor (PMSM) speed control. The improved FNN-PI controller has a compact structure and used for gradient descent algorithm. Experimental results have shown excellent tracking performance of the proposed FNN-PI controller, and have convincingly demonstrated the usefulness of the proposed controller in industrial drives with uncertainties.
Keywords: Fuzzy neural network controller; Sugeno model; Permanent magnet DC motor; Motor drive